2023
DOI: 10.1002/asia.202300111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Ca Doping On The CO2 Hydrogenation Performance Of CaxZn10‐xFe20 Catalysts (x=0, 0.5, 1 and1.5)

Abstract: In this paper, CaxZn10-xFe20 catalysts were prepared by the co-precipitation method and applied to CO 2 hydrogenation. The experimental results show that the CO 2 conversion of the catalyst Ca1Zn9Fe20 at a Ca doping amount of 1 mmol can reach 57.91 %, which is 13.5 % more than the CO 2 conversion of the catalyst Zn10Fe20. Moreover, the catalyst Ca1Zn9Fe20 has the lowest selectivity for both CO and CH 4, with 7.40 % and 6.99 %, respectively. The catalysts were characterized by XRD, N 2 adsorption-desorption, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…On one hand, they can promote the dispersal, reduction, and carburization of Fe species and improve the stability of the FeC x active phase. On the other hand, the electron transfer from promoters to Fe species weakens the C–O bonds and inhibits the H 2 dissociation, thus favoring the formation of olefins and long-chain hydrocarbons. Moreover, it was also found that CO 2 on MgO surfaces can be activated into carbonate substances, and Mg x -H complexes have stronger electron-donating effects, which can promote the formation of *HCOO, a critical intermediate species in the CO 2 hydrogenation reaction . Thus, it is critical to regulate the adsorption of reactants and the electronic structure of active sites to realize the effective coupling of RWGS and FTS reactions.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, they can promote the dispersal, reduction, and carburization of Fe species and improve the stability of the FeC x active phase. On the other hand, the electron transfer from promoters to Fe species weakens the C–O bonds and inhibits the H 2 dissociation, thus favoring the formation of olefins and long-chain hydrocarbons. Moreover, it was also found that CO 2 on MgO surfaces can be activated into carbonate substances, and Mg x -H complexes have stronger electron-donating effects, which can promote the formation of *HCOO, a critical intermediate species in the CO 2 hydrogenation reaction . Thus, it is critical to regulate the adsorption of reactants and the electronic structure of active sites to realize the effective coupling of RWGS and FTS reactions.…”
Section: Introductionmentioning
confidence: 99%